2019
DOI: 10.11114/jets.v7i3.3914
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Students’ Special Curiosity in Sports Based on Some Demographic Variables

Abstract: The present study aims to determine special curiosity in sports among students who study at different university departments. The population of the study consists of students studying at different departments at Yozgat Bozok University during 2018-2019 academic year. The sample of the study consists of 397 students who study at different departments at Yozgat Bozok University during 2018-2019 academic year and voluntarily participated in the online survey sent them by e-mail. Survey was used as a data collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…The results also show that there is a positive correlation between the level of curiosity and the use of learning strategies [5]. This curiosity allows a person to seek answers, explore problems, observe their environment, and understand events that are taking place in the world [6]. From these various opinions, it can be concluded that the importance of curiosity is that it can benefit students and can make students active in learning, thus gaining new knowledge and skills and obtaining important information for successful learning.The theoretical model of curiosity is divided into two dimensions.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The results also show that there is a positive correlation between the level of curiosity and the use of learning strategies [5]. This curiosity allows a person to seek answers, explore problems, observe their environment, and understand events that are taking place in the world [6]. From these various opinions, it can be concluded that the importance of curiosity is that it can benefit students and can make students active in learning, thus gaining new knowledge and skills and obtaining important information for successful learning.The theoretical model of curiosity is divided into two dimensions.…”
Section: Introductionmentioning
confidence: 77%
“…The previuos study showed a positive relationship between curiosity and motivation [5]. Another study showed that there were significant differences in curiosity based on gender, majors, and monthly expenses [6]. Other studies have shown that perceptions of teaching styles contribute to students' curiosity and motivation to be active in the classroom [9].…”
Section: Introductionmentioning
confidence: 97%